Evaluation of composting a different compositions to take advantage of organic waste domestic puno city as a measure to contribute in counter climate change - Huapaya Cruz, Yury Hamilton (2024)
Compost piles were evaluated at different compositions to take advantage of household organic waste from the city of Puno in the period from June to September 2015. Three compost piles were evaluated at different composition and one cell vermiculture without worms, in order to determine what conditions produce an organic fertilizer higher quality, using organic waste Domiciliarios (ROD), Poda of Parks and Gardens of the city (PPJ) and sheep Dung (EGO), the three compost piles with a volume of 4.5 m3; P4 has 100% of 0.8 m3 ROD placed in a cell vermiculture and P5 has 100% ROD 2.6 m3 which was located on the outside of the plant. To accelerate decomposition, an infrastructure greenhouse conditions. After three months, three samples of P1, P2, P3 and P4 was removed and taken to the laboratory. The parameters were compared with the analysis of variance, the pile contains more Nitrogen, %Organic Matter and Solido Totals is P4. P4, sulfur is added to 1% weight, to neutralize the pH. As for the %humidity, no significant difference of the four piles. For agriculture, will have to be used in large quantities for example for request of N of 160Kg/Ha, you have to use 4.38tons/ha of compost to cover this need, which it is feasible, since, in the city of Puno, it is generated 50 tons/day of ROD, which is 37.5 tons/day of compost and a year is 13687.5 tons of compost, enough to cover 3125 ha/year of farmland.